Faktor –Faktor yang Mempengaruhi Anemia pada Ibu Hamil - Dian Shofia Reny Setyanti; Iin Tri Marlinawati (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
The maternal mortality rate (MMR) is an indicator of the success of health services in Indonesia. Maternal mortality can indicate that maternal mortality can occur due to anemia. The maternal mortality rate is 60% for anemic mothers and 19.9% ​​for those who are not anemic. The purpose of this study was to determine the risk factors for anemia in pregnant women at PMB T, Rembang in 2024. The type used was a retrospective cohort study and the statistical test used in this study was the Chi-square test. The population in this study were all pregnant women who were recorded in the Medical Records of PMB T in 2024 as many as 151 people with a total sample of 60 respondents who were taken by random sampling method. The results showed that there was a relationship between mother's education (p.value = 0.002), mother's occupation (p.value = 0.002), age (p.value = 0.003) and nutritional status (p.value = 0.021) with the incidence of anemia in pregnant women in PMB T. The conclusion of this study is that education, occupation, age and nutritional status are related to the incidence of anemia in pregnant women. Suggestions are that it is hoped that health workers can increase knowledge in the community, especially pregnant women by providing counseling or counseling about the problem of anemia.